(untitled) (Historia, 2021)
At the end of the nineteenth century, the actions of belligerents were constrained by the Hague Convention of 1899 and the Geneva Convention of 1864. The Hague Convention differentiated between combatants and non-combatants, but both the British implementation of a scorched earth policy and the Boer execution of blacks violated this convention. The Geneva Convention centred on medical immunity, which presupposes medical neutrality. The British opposed the voluntarism fundamental to the Red Cross movement and all British medical personnel in the field were subservient to the military establishment. Imperial patriotism, the shortcomings of the army and the insistent claims of military necessity subverted best medical practice, producing dilemmas that doctors had to negotiate. On the Boer side too, there was the moral complexity of doctors who were not only medical professionals but also social agents with personal commitments. This article considers the dilemmas that confronted doctors involved in the South African War in the Free State and concludes that trends in dealing with ethical challenges in this war became normative in subsequent conflicts.